Trash management using “asset based community-driven development” to turn garbage into commodity with creative-economic value - Subiyantoro Subiyantoro; Siti Zubaidah; Taufiq Ahmad Syauqi (International Journal of Health Science and Technology, 2020)
Education is still not answer the expectations of the people, they always questioned the relevance of education by a variety of community needs in the dynamics of economic, social, political, legal and cultural. A new paradigm of education changes to quality (quality oriented) is one of the strategies to achieve educational excellence in meeting the demands and needs of the community. Therefore necessary institutional strengthening capacity (Capacity Building) of the Madrasah. Community empowerment-based creative economy programme through the madrasah were necessary.  One of the selected empowerment utilizing waste products worth selling. On the other side of the creative economy approach is thew into madrasah quality improvement effort in answering the needs of the community in the era of economic globalization. This research aims to improve the quality of economic empowerment through creative schools that work together with the community. The subject of this research is MTs. N. 5 Kulon Progo, located in the village and brought in, (environmental mountain tourism Suroloyo), Ma'arif myocardial infarction and Pagerharjo village (pagerharjo village Government Center neighborhood is located), myocardial infarction and Ngargosari Ma'arif, community mothers dukuh Ngargosari Ngaliyan, Dukuh Trayu Community Ngargosari. The research method used was applying a Research and Development (RD), with regard to data collection Techniques: observation, indept interview. The strategy of training/mentoring in applying the model of "service learning", with the approach of andragogy. The data analysis used models, Miles and Huberman and Spradley. The results of this study indicate that the training provided to communities and schools to cultivate waste into creative stuff that has value has managed to provide the skills knowledge and abilities are new to them. The subject is able to make a variety of creative stuff from the trash so that gave rise to the idea for the creation of the trash bank as the flagship program in the schools to have better quality.